DEVELOPMENT OF FLIPPED DIGITAL LEARNING MEDIA FOR THE HUMAN RESPIRATORY SYSTEM CLASS VIII - Azizah, Lina Nur; Andri Wahyu Wijayadi (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2025)
Abstract: The aim of this research is to develop Flipped Digital media as a learning medium at SMP Negeri 5 Jombang on the subject of the human respiratory system. The research uses the ADDIE development model which is an abbreviation for Analyze, Design, Development, Implementation and Evaluation. The Flipped Digital media was developed, validation and practicality tests were carried out to measure the suitability of the learning media. Validation tests were carried out by media and material expert lecturers and science teachers, then practicality tests were carried out by distributing student response questionnaires. The results of the research show that the Flipped Digital learning media on the human respiratory system material was declared very valid by the validators with a percentage of 97.31. Meanwhile, based on the results of the student response questionnaire. Flipped Digital media was stated to be very practical with a percentage of 95.28. Thus, it can be concluded that Flipped Digital media is declared very valid and practical, so it is suitable for use in learning.